Biografen som mötesplats - Carina Sjöholm (Kulturella perspektiv, 1994)
The subject of this study is a medium — the cinema — and a situation — going to the movies. It is more specifically the latter, i.e. the cinema as an arena for cultural confrontations, which is discussed. It is reasonable to suppose that cinema-going at the time (the 40s and 50s) played an important role in cultural complexity, which among other things included a longing for the city (or that which was separated from the countryside), and the creation of a public sphere. Cinema-going became an element in a learning process, both an exercise in reflexivity where one could see oneself mirrored in the others, and the creation of media competence. To go to the movies was to be a part of a festivity pattern, where the film in itself was not the most important thing. By coming together, and to a certain extent in the reception of the film, youth gained a feeling of possibility. These meetings became a marketplace for exchange and negotiation. As far as I can see it was a creative and dynamic meeting, where one was trained to see the arriving future — an era different from the past.